Hazard Identification, Risk Assessment, and Risk Controlling Using Hazard Identification and Risk Assessment Method. (August 2019) - Aulia, R; Qurtubi,
Abstract: This article discusses about hazard identification, risk assessment and risk controlling in a production line 1 in PT. XYZ, a company that focuses its production in engineering, production, installation (EPI) of concrete industry. Observation and interview are employed as the method of data collection. The analysis involves Hazard Identification and Risk Assessment. Based on hazard identification, there are 53 potential hazard occurrences that possibly could emerged in PT. XYZ, consist of mechanical hazards with 55%, physical hazard of 32%, chemical hazard of 9% and electrical hazard 4%. Risk potential is calculated as 53% at the high level, 34% at the moderate level, 11% at the extreme level and 2% at the low level. The controlling that could be implemented are: the operational process that should fulfil IK (Work Instruction); the maintenance of alternative tools that fit with lifting capacity; scheduled maintenance, the instalment of signs, utilization of safety helmet, mask, earplug, safety shoes and gloves; the appropriate usage of tool as its ideal capacity; to equip operators with SIO, to secure the position of workers away from railway, maintaining the edge of mold clean from seplit and stirring materials; to secure the position of the workers away from impact tool range; to install the ladder inside the steam vessel; to maintain the steam pipe with safe wrapper; to provide the APAR; to set the pressure of oxygen/LPG; to install the switch and plug-in; to maintain the electricity cable network well-wrapped with no leaks; to utilize strong wood material for foothold; installing SPOT HPIT lamp at the line 1.